2020
DOI: 10.3390/v12080825
|View full text |Cite
|
Sign up to set email alerts
|

Crocetin Improves Dengue Virus-Induced Liver Injury

Abstract: Dengue virus (DENV) infection is one of the most widespread mosquito-borne viral infections. Liver injury is commonly observed in severe DENV infection, and the present study aimed to examine the efficacy of crocetin treatment in an immunocompetent mouse model of DENV infection exhibiting liver injury. The efficacy of crocetin treatment in DENV-induced liver injury was assessed via both transaminase levels and histopathology analysis. A real-time polymerase chain reaction array was then used to describe the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Dhar et al ( 23 ) used hemorrhagic shock mice to confirm the protective effect of crocetin on survival and liver tissue damage. Sreekanth et al ( 24 ) found that crocetin could improve dengue virus-induced liver injury but could not suppress virus replication. As a traditional drug, crocetin is considered to have benefits on the nervous system, protective effects from cardiovascular disease, antioxidation, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…Dhar et al ( 23 ) used hemorrhagic shock mice to confirm the protective effect of crocetin on survival and liver tissue damage. Sreekanth et al ( 24 ) found that crocetin could improve dengue virus-induced liver injury but could not suppress virus replication. As a traditional drug, crocetin is considered to have benefits on the nervous system, protective effects from cardiovascular disease, antioxidation, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting investigation, 4 was shown to improve Dengue virus (DENV)‐induced liver injury in immunocompetent mouse model of DENV infection with observed liver injury without any significant effect on viral load (Sreekanth et al, 2020 ). Major inhibitory effects were observed on DENV‐induced apoptosis, pro‐inflammatory cytokine expressions and NF‐κB nuclear translocation.…”
Section: Introductionmentioning
confidence: 99%
“…( 42 ). In studies of liver diseases, CCT showed comparative beneficial effects on CCL 4 -induced and dengue virus-induced liver damage via induction of antioxidant defense ( 43 , 44 ). In this study, the therapeutic targets of crocin I, crocin II, and CCT were combined, because orally administered crocins are hydrolyzed to CCT before they are incorporated into the blood circulation, and these findings have been confirmed in several pharmacokinetic studies ( 45 47 ).…”
Section: Discussionmentioning
confidence: 99%